Lacrosse for Reconciliation: How Lacrosse Organizations in Canada Have Taken Up the Truth and Reconciliation Commission’s Calls to Action - Holmes, Avery (Université d'Ottawa / University of Ottawa, 2023)
In 2015, The Truth and Reconciliation Commission (TRC) released a list of Calls to Action aimed at redressing the harms of the residential school system through improving and reconciling relationships between Indigenous and non-Indigenous communities in Canada. Within these Calls to Action, there are five Calls that directly address sport. Lacrosse, as a sport currently dominated by white men, is an Indigenous physical practice that has been, and continues to be, widely appropriated by settlers. This ongoing legacy of settler colonialism positions lacrosse as a pressing site through which to investigate reconciliatory efforts. Further, the current landscape of lacrosse as a white male dominated sport, coupled with the ongoing cultural appropriation of lacrosse from Indigenous communities, creates an important opportunity to investigate interlocking systems of settler colonization and heteropatriarchy within sport. These areas are considered through the publishable papers of my thesis. The questions that have guided my Master’s of Arts by publishable paper are two-fold: how are national and provincial lacrosse organizations in Canada taking up the TRC’s sportrelated Calls to Action, and in what ways are these efforts gendered? Chapter 2, the first of my publishable papers, I argue that these Calls to Action need to be extended to lacrosse organizations within Canada. In this chapter, I investigate how representatives from seven lacrosse organizations within Canada conceptualized their organizations as attending (or not) to the Calls to Action. In Chapter 3, in which I present the second of my publishable papers, I focus on the gendered elements of the participants’ responses to how lacrosse organizations have taken up the Calls to Action and have addressed Indigenous women’s involvement in lacrosse.
Keywords: Reconciliation; Lacrosse